Upgrading end-of-line residues of the red seaweed Gelidium sesquipedale to polyhydroxyalkanoates using Halomonas boliviensis - Tuna, Stepan (2020)
Agar extraction from Gelidium and Gracilaria red seaweed species produces hundred thousand ton of carbohydrate-rich residues annually. Gelidium sesquipedale waste biomass obtained after agar extraction, still contained 44.2 % w/w total carbohydrates (dry-weight basis). These residues were biologically up-graded to poly-3-hydroxybutyrate (P3HB) after saccharification of their carbohydrate fraction to simple sugars. A combined hydrolysis treatment using sulfamic acid followed by enzymatic hydrolysis with cellulases produced a glucose-rich hydrolysate with a negligible content of inhibitors. With this treatment a sugar yield of circa 30 % (g glucose/g biomass) was attained. The algal hydrolysates were assessed as carbon source for the production of P3HB by the halotolerant bacteria Halomonas boliviensis. A cell concentration of 8.3 g L−1 containing 41 % (w/w) of polymer and a yield (YP/S) of 0.16 gpolymer/gglucose were attained in shake flask assays. In this work, cellulose-rich seaweed waste was shown to be an upgradable, sustainable source of carbohydrates.